Social impact of the DEVIDA program on agricultural and environmental development in the Inambari basin, Puno - Peru - Tumi Quispe, Jesús (2019)
The objective was to analyze the social impact of the interdiction program of coca cultivation promoted by DEVIDA on agricultural and environmental development in the Inambari Puno-Peru basin. The study has a non-experimental, sectional, descriptive, qualitative and micro level character. The operational population, determined by convenience sampling and saturation, was made up of executives from the peasant patrols and the association of agrarian producers of the Inambari basin. The techniques of data collection were the revision of the legal-legal framework and international agreements on interdiction and alternative development, in-depth interviews and participant observation. The social impact of the DEVIDA program on agricultural and environmental development in the Inambari basin according to the legal-legal framework and the vision of the agrarian producers is negative, given that its intervention strategy and methodology not only failed, but also brought with it crisis for the inhabitants of the area, due to the fact that, in its purpose of avoiding the replanting of coca in intervened areas, it promoted the use of chemical fertilizers for the adaptation and cultivation of alternative products. The interdiction supposed a rupture of the human experience with the ecological and sociocultural environment, denoting that the intervention carried out by DEVIDA-CORAH was inadequate, because the forced eradication not only worsened the precarious family economy and dynamized the migratory process, but also impacted negatively on the environment and the capacity of the arable lands, making them unproductive due to the contamination and proliferation of fungi and the irrational introduction of chemical fertilizers.